2016
DOI: 10.1016/j.rbre.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Poor muscle strength and function in physically inactive childhood-onset systemic lupus erythematosus despite very mild disease

Abstract: Physically inactive C-SLE patients with very mild disease showed reduced muscle strength and functionality when compared with healthy controls matched by physical activity levels. These findings suggest C-SLE patients may greatly suffer from a physically inactive lifestyle than healthy controls do. Moreover, some sub-clinical "residual" effect of the disease or its pharmacological treatment seems to affect C-SLE patients even with a well-controlled disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…Cheung et al showed skeletal muscle mitochondrial dysfunction in SLE patients 4 . Similar to our findings, Pinto et al found weaknesses in the leg and hand grip muscles of SLE patients 7 . Andrews et al also found reduced muscle strength (evaluated knee extension and flexion) which might be associated with impaired physical activity 9 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Cheung et al showed skeletal muscle mitochondrial dysfunction in SLE patients 4 . Similar to our findings, Pinto et al found weaknesses in the leg and hand grip muscles of SLE patients 7 . Andrews et al also found reduced muscle strength (evaluated knee extension and flexion) which might be associated with impaired physical activity 9 .…”
Section: Discussionsupporting
confidence: 92%
“…Studies evaluating peripheral skeletal muscle abnormalities are commonly focused on the quadriceps femoris muscle and hand-grip muscles. Few studies have demonstrated that the quadriceps femoris is weakened 4 7 9 , however, to the best of our knowledge; no one has investigated specific upper extremity muscle strength. In our study, we found that upper and lower extremity muscle and hand grip strengths were decreased in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no other study, according to our knowledge, that evaluates the SarQoL total score in SLE subjects with low muscle function. Several studies showed that low muscle strength was consistently related to lower quality of life (SF-36), 9 life satisfaction (value-added activity, VLA), 9 fatigue, 23 and depression 6 in SLE subjects. Improvement of quality of life in SLE subjects with low muscle function through physical exercise and nutritional intervention, although promising, still marred with several limitations, such as small sample size, no reasonable control, contradictive results, short monitoring time, and unspecific health-related quality of life tools used.…”
Section: Discussionmentioning
confidence: 99%